2018
DOI: 10.1093/mnras/sty2799
|View full text |Cite
|
Sign up to set email alerts
|

A Zeldovich reconstruction method for measuring redshift space distortions using cosmic voids

Abstract: Redshift space distortions (RSD) in the void-galaxy correlation ξ s provide information on the linear growth rate of structure in low density environments. Accurate modelling of these RSD effects can also allow the use of voids in competitive Alcock-Paczynski measurements. Linear theory models of ξ s are able to provide extremely good descriptions of simulation data on all scales provided the real space void positions are known. However, by reference to simulation data we demonstrate the failure of the assumpt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(79 citation statements)
references
References 74 publications
2
77
0
Order By: Relevance
“…Our model for the void-galaxy cross-correlation has previously been extensively tested using this mock galaxy sample in the full cubic simulation box with periodic boundary conditions [25,26]. To account for survey edge effects, we create a single 'CMASS-like' mock catalogue from this cubic box.…”
Section: N -Body Mocksmentioning
confidence: 99%
See 3 more Smart Citations
“…Our model for the void-galaxy cross-correlation has previously been extensively tested using this mock galaxy sample in the full cubic simulation box with periodic boundary conditions [25,26]. To account for survey edge effects, we create a single 'CMASS-like' mock catalogue from this cubic box.…”
Section: N -Body Mocksmentioning
confidence: 99%
“…The anisotropic galaxy distribution around cosmic voids can also be used as an Alcock-Paczynski test [17], and to measure the growth rate [18][19][20][21][22][23][24][25][26][27][28]. As voids are regions of low density, if the void is large enough to dominate over environmental effects from nearby structures, the average galaxy velocity in the void vicinity is directed outwards from the void centre.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of their low matter content, voids become dominated by dark energy at early times, and so are sensitive to its nature (Lee & Park 2009;Lavaux & Wandelt 2012;Bos et al 2012;Pisani et al 2015). The dynamics within voids can be accurately modelled by linear perturbation theory even on small scales (Cai et al 2016;Nadathur & Percival 2019;Nadathur et al 2019a), which provides a unique opportunity to measure the growth rate of structure through redshift-space distortions (RSD) in the distribution of galaxies around voids (some examples of these studies in survey data include Hamaus et al 2016;Hawken et al 2017;Achitouv et al 2017;Nadathur et al 2019b). A recent analysis by Nadathur et al (2019b) of the redshift-space void-galaxy correlation observed in the Baryon Oscillation Spectroscopic survey (BOSS; Dawson et al 2013) showed that in combination with galaxy clustering, this method reduces the uncertainty in the measurement of cosmological distance scales by 50% compared to previous results arXiv:1911.08475v2 [astro-ph.CO] 21 Jan 2020 based on baryon acoustic oscillations (Alam et al 2017).…”
Section: Introductionmentioning
confidence: 99%